Teaching english a foreign language to a visually impaired student at "Escuela de Educación Básica Particular Liceo Panamericano Centenario". - Defaz Moreno, Andrea Michelle (2018)
This research paper has as aim to explore the needs of a visually impaired student EFL skills acquisition at “Escuela de Educación Básica particular Liceo Panamericano Centenario”. The study will provide teachers some suggestions on how to develop adapted material for the English classes through the use of assistive technology and offer the institution key points as to how train teachers properly on inclusive education, in this case for the visually impaired individuals. The data was collected through interviews and surveys; they were applied to three English teachers of a visually impaired student at the aforementioned institution. The findings provide important evidence as to what is failing in the institution regarding the correct implementation of adapted material in this subject. Recommendations were provided on what assistive technology the institution should acquire to properly aid the teachers and enhance the learning environment of the visually impaired student. Thus, providing a background for any further research to be made on the topic of visual impairment and second language acquisition, materials, adaptations, modifications or techniques to have successful outcomes as results.